Analisis Kepemimpinan Partisipatif dalam Pengendalian Kebakaran Hutan dan Lahan - Andreastuti, Desie (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
Tropical forests in Palangka Raya city is a tremendous asset given the forest can provide economic benefits as a Pendapatan Asli Daerah (PAD) in addition it is also the sector with the most potential as a source of livelihood and life for society and private plantation companies. However, the existence of forests are currently threatened due to forest areas that were once green became barren and the barren region mainly caused by human activity that is destruction and burning the land. Land and forest fires occur each year into problems and threats faced by the multidimensional impact forests. For supporting local government in realizing land and forest fire control, based on Peraturan Pemerintah No. 7 of 2003 is related to the preparation of the land and forest fire control and decision of the Mayor of Palangkaraya No. 11 of 2008 while the duties and functions of the head of Badan Lingkungan Hidup (BLH) by Peraturan Walikota Palangkaraya No. 17 of 2012 on job descriptions positions of Chairman of BLH Palangkaraya is formulating operational policy, controling, developing, organizing, coordinating and providing technical services in the field of environmental management are integrated with the relevant agencies in accordance with the provisions and applicable the laws. .